Smart Substation VLAN Configuration Method Based on Improved Search Tree - Zhang, Hongtao; Liu, Yuntao; Zou, Gang; Jiang, Zikai; Huang, Wei; Zhou, Kunjun (2024 9th Asia Conference on Power and Electrical Engineering (ACPEE), 2024)
A smart substation VLAN configuration method based on improved search tree is proposed to address the problem of network uncertainty caused by the lack of unified standards for VLAN partitioning and configuration methods. Firstly, a communication network model for VLAN configuration is established based on the topology of the smart substation communication network and the subscription relationship between devices. Then, combined with the VLAN model, the search tree algorithm is improved using the heuristic path cost concept, and it is used to determine the situation where the packet transmission path passes through the switch port. Finally, based on the Tag mechanism, a VLAN partitioning scheme is proposed and switch port setting rules are set, combined with the determined packet transmission path to complete the VLAN configuration. Based on the experimental analysis of a 220kV smart substation, the improved search tree algorithm has an average time and average path length of only 0.25s and 846m, and the obtained VLAN configuration method has lower packet subscription relationship necessity index values and port traffic than other methods, indicating strong practicality.